The Emotional Recession: global declines in emotional intelligence and its impact on organizational retention, burnout, and workforce resilience - Freedman, Joshua M.; Freedman, Patricia E.; Choi, Daniel Y.; Miller, Michael (Frontiers in Psychology, 2025)
IntroductionThe COVID-19 pandemic triggered widespread disruptions to workplace wellbeing and employee engagement, intensifying risks of burnout and reduced retention. Although organizational performance has been widely studied, few investigations have examined longitudinal declines in emotional intelligence (EQ) during the pandemic and its aftermath or considered their implications for organizational resilience.MethodsThis study analyzed EQ trends from 2019 to 2024 using data from the Six Seconds Emotional Intelligence Assessment (SEI), a validated 77-item instrument measuring eight core competencies and four life outcome factors. The stratified sample comprised 28,000 adults across 166 countries.ResultsGlobal EQ scores declined by 5.79% (Cohen’s d = 0.22, 95% CI [0.17, 0.27]), with statistically significant decreases across all eight competencies (p < 0.001). The largest declines occurred in Drive-related skills, including Engage Intrinsic Motivation (Cohen’s d = 0.22, 95% CI [0.17, 0.27]), Exercise Optimism (Cohen’s d = 0.23, 95% CI [0.18, 0.28]), and Pursue Noble Goals (Cohen’s d = 0.19, 95% CI [0.14, 0.24]). Success Factors—Effectiveness (Cohen’s d = 0.20, 95% CI [0.15, 0.25]), Relationships (Cohen’s d = 0.19, 95% CI [0.14, 0.24]), Quality of Life (Cohen’s d = 0.17, 95% CI [0.12, 0.22]), and Wellbeing (Cohen’s d = 0.13, 95% CI [0.08, 0.18])—declined by 4.39–6.45%. Individuals with higher EQ were 10.18 times more likely to report strong overall life outcomes (OR = 10.18, 95% CI [9.64, 10.76]).DiscussionThese findings reveal an “Emotional Recession,” a sustained global decline in emotional and relational capacities with direct implications for wellbeing, engagement, and organizational resilience.